Job Creation, Small vs. Large vs. Young, and the SBA - J. David Brown; John S. Earle; Yana Morgulis (Institute for the Study of Labor (IZA), 2015)
Analyzing a list of all Small Business Administration (SBA) loans in 1991 to 2009 linked with annual information on all U.S. employers from 1976 to 2012, we apply detailed matching and regression methods to estimate the variation in SBA loan effects on job creation and firm survival across firm age and size groups. The number of jobs created per million dollars of loans generally increases with size and decreases in age. The results imply that fast-growing firms ("gazelles") experience the greatest financial constraints to growth, while the growth of small, mature firms is least financially constrained. The estimated association between survival and loan amount is larger for younger and smaller firms facing the "valley of death".
Keywords: H81; 330; job creation; firm survival; credit constraints; small businesses; government loan guarantees